Youth and citizenship: usage of digital media at the NGO Aldeia, in Fortaleza - Cogo, Denise (2013)
The article examines the citizen communication processestissues by young working in association Aldeia, in Fortaleza, Ceará. Theresearch is theoretical studies of social movements, digital media and citizencommunication. Selected as a result of the research, three aspects of the uses oftechnology by Aldeia young participants: 1) the absence of greater criticality inreading the media; 2) the complementarity between analog and digital media;and 3) the demand for professionalism